Do This in Remembrance of Me Online?: Irenic and Elenctic Normativity in Liturgical Studies - Barnard, Marcel (Yearbook for ritual and liturgical studies, 2020)
The authors of this article, two liturgical scholars and a scholar in dogmatics, engaged in a public discussion of whether or not a Holy Communion should be celebrated online. Speaking about the case afterwards, they found that both the discourse of liturgical studies and of dogmatics introduced comparable normative elements. Barnard and Klomp in liturgical studies speak with Ronald Grimes of "ritual criticism" and with Roy Rappaport of "The True Words" as benchmarks that are established by religions in the infinite field of meanings of the rite. Wisse speaks on the basis of the originally Lutheran distinction of Law and Gospel of therapeutic or irenic and elenctic normativity. The authors advocate this distinction as an instrument that opens the way for a discussion about the mystery of life and of the sacraments.